THE IMPACT OF SCHOLAR'S DIFFERENCES IN DETERMINING THE STATUS OF HADITH ON THE LAW OF MARRIAGE GUARDIANS AND DOWRIES - Afabih, Abdillah; Roziqi, Achmad; Maulana, Anas (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
The different methods of scholars in determining the status of traditions have a significant impact on the formulation of Islamic law. This study discusses the disputed hadiths in Bidāyat al-Mujtahid, especially in the book of al-Nikāḥ, and their implications for the law of marriage guardians and the minimum standard of dowry. This research uses the literature review method by tracing and analyzing the hadiths of disputed status. The results show that there are two main hadith that are disputed by scholars. while the standard minimum dowry hadith is also rejected by the majority of scholars due to the weakness of its narrators. These differences have implications for Islamic law, particularly in the regulation of marriage guardians and dowries in various Muslim countries. This study contributes to understanding the role of hadith criticism in the formulation of Islamic law. However, this study is limited to an analysis of Bidāyat al-Mujtahid and has not examined the implementation of the law in various Muslim countries. Further studies are needed to explore the application of hadith criticism methodology in contemporary legal systems. [Perbedaan metode ulama dalam menilai keabsahan hadis berdampak signifikan terhadap formulasi hukum Islam. Penelitian ini mengkaji perbedaan penilaian ulama terhadap dua hadis dalam Bidāyat al-Mujtahid, khususnya dalam kitab al-Nikāḥ, serta pengaruhnya terhadap hukum wali nikah dan standar minimal mahar. Kajian ini menggunakan metode kajian kepustakaan dengan pendekatan analisis isi (content analysis), menelusuri serta menganalisis hadis-hadis yang diperdebatkan statusnya. Hasil penelitian menunjukkan bahwa terdapat dua hadis utama yang diperselisihkan derajatnya oleh para ulama. Hadis pertama tentang kewajiban wali dalam pernikahan dinilai lemah oleh Mazhab Hanafi, sedangkan hadis standar minimal mahar juga ditolak oleh jumhur ulama karena kelemahan perawinya. Perbedaan ini berdampak pada hukum Islam, khususnya dalam regulasi wali nikah dan mahar di berbagai negara Muslim. Kajian ini berkontribusi dalam memahami peran kritik hadis dalam formulasi hukum Islam. Namun, penelitian ini terbatas pada analisis Bidāyat al-Mujtahid dan belum mengkaji implementasi hukum di berbagai negara Muslim. Studi lanjutan diperlukan untuk mengeksplorasi penerapan metodologi kritik hadis dalam sistem hukum kontemporer.]